The Legal Genealogy of the Duty to Accommodate American and Canadian Workers with Disabilities: A Comparative Perspective - Ravi Malhotra (Washington University Journal of Law & Policy, 2007)
In this Essay, I seek to analyze the origins of the duty to accommodate people with disabilities in Canadian law in order to present a counter-factual argument on why the duty to accommodate has not flourished in American law. Comparative legal approaches have the merit of shedding fresh light on old legal problems that might not otherwise be considered. In Part I, I trace the history of the concept of reasonable accommodation in leading Supreme Court of Canada decisions, and demonstrate how accommodation of workers with religious beliefs remained central to the development of the jurisprudence and helped make decision-makers more comfortable in adopting a broader theory of equality. I contrast this in Part II with American jurisprudence on the duty to accommodate workers with religious beliefs, which has been plagued by concerns that the mandatory nature of reasonable accommodation in the workplace may infringe the Establishment Clause. I conclude in Part III with some brief reflections on the implications of the argument.
Keywords: Discrimination against people with disabilities; People with disabilities – Employment; Duty to accommodate (Law); Discrimination in employment – United States; Church and state; Disabled persons; Employment discrimination; Handicapped discrimination; Americans with Disabilities Act of 1990; Workplace Religious Freedom Act of 2002; Canada; United States